?? ? TRACE ELEMENTS IN INDIGENOUS MEDICINALPLANTs (RHAzYA STRICTA, VINCA ROSEA ANDFAGONIA CRETICA): Short Communication - Fatima, Kaneez; Shirin, Khaula; Kalhoro, Mahboob Ali; Qadiruddin, Muhammad; Badar, Yasmeen (Biological Sciences - PJSIR, 1999)
belonging to Apocynaecea and Zygophyllaecea families respectively (Hooker 1882) which are grown all over pakistan and have anticancer property (Watt 1890; Chakraborti and Mukherji 1968; Siddiqui and Bukhari 1972).